Donald Judd : writings - Judd, Donald; Judd, Flavin; Murray, Caitlin, 1984-; Judd Foundation; David Zwirner (Gallery) (New York : David Zwirner Books, 2016)
"Donald Judd writings", copublished by Judd Foundation and David Zwirner Books, is the most comprehensive collection of the artist's writings assembled to date. This timely publication includes Judd's best-known essays organized chronologically with little-known texts previously published in limited editions. This new collection also includes unpublished college essays and hundreds of never-before-seen handwritten notes, a critical but unknown part of Judd's writing practice. Judd's earliest published writing, consisting largely of reviews for hire, defined the terms of art criticism in the 1960s, but his essays as an undergraduate at Columbia, published here for the first time, contain the seeds of his later writing, and allow readers to trace the development of his critical style. The writings that followed Judd's early reviews are no less significant art-historically, but have been relegated to smaller publications and have remained largely unavailable until now. The largest addition of newly available material is Judd's unpublished notes--transcribed from his handwritten accounts of and reactions to subjects ranging from the politics of his time, to the literary texts he admired most, from complaints about pluralism in art to his admiration for Giambattista Vico, and through him, Lucretius. In these intimate reflections we see Judd's thinking at its least mediated--a mind continuing to grapple with questions of its moment, demonstrating the intensity of thought that continues to make Judd such a formidable presence in contemporary art.
Josef Albers, 1991 -- Notes, January to February 1992 -- Letter to the Editor, 19 February 1992 -- Notes, March to December 1992 -- Cacalomilli, 1992 -- Art and Internationalism, 1992 -- Fine Art and Commercial Architecture, 1992 -- Monument to the Last Horse: Animo et Fide, 1992 -- Notes, January 1993 -- 21 February 1993 -- Notes, February to November 1993 -- It's Hard to Find a Good Lamp, 1993 -- Some Aspects of Color in General and Red and Black in Particular, 1993 -- Images -- Index.
Imported from: lx2.loc.gov:210/LCDB (Do not remove)
boek
Keywords: Judd, Donald; 1900-1999